The Innovative Learning of Social Arithmetic using Realistic Mathematics Education Approach - Rahayu, Winda; Prahmana, Rully Charitas Indra; Istiandaru, Afit (Universitas Hamzanwadi, 2021)
Learning mathematics has a significant contribution to the students’ daily activities, one of which is on social arithmetic topic. The implementation of social arithmetic, in general, is mostly found in buying-selling and banking activities. However, students still find difficulties in understanding this topic. It is because the teaching and learning activities still use a conventional approach, which restricts the students to imagine how it is implemented in daily life. Therefore, this paper aims to describe the innovative learning activities of social arithmetic among junior high school students using the Realistic Mathematics Education (RME) approach. This research was conducted in three meetings, and the researcher acted as the teacher in the class. The results showed that the innovative learning of social arithmetic using the RME approach and word problems could improve the students’ learning outcomes with an average score of 81.92% and 92.59% of the total of students scored above passing grade.